Activating transcription factor 3-activated long noncoding RNA forkhead box P4-antisense RNA 1 aggravates colorectal cancer progression by regulating microRNA-423-5p/nucleus accumbens associated 1 axis. Issue 2 (1st February 2022) - Cheng, Zhouyang; Jiang, Song; Tao, Ran; Ge, Haipeng; Qin, Jun
ABSTRACT: Long noncoding RNAs (lncRNAs) have vital roles in the progression of colorectal cancer (CRC). Forkhead box P4-antisense RNA 1 (FOXP4-AS1) showed a potential unfavorable prognostic factor for CRC, while its underlying mechanism remains elusive. Thus, the goal of this research is to determine mechanism of FOXP4-AS1 in CRC occurrence and development. Herein, a Dual-luciferase reporter assay was performed to assess the regulation of miR-423-5p to nucleus accumbens-associated protein 1 (NACC1) and activating transcription factor 3 (ATF3) to FOXP4-AS1 promoter. Hematoxylin-eosin (H&E) staining was performed to detect the pathological changes of tumor tissues. Flow cytometry, cell counting kit 8, Transwell, and wound healing assays were conducted to assess apoptosis, proliferation, migration, and invasion of CRC cells, respectively. The results showed that FOXP4-AS1 was highly expressed in CRC cell lines and tissues. CRC progression was promoted by the overexpression of FOXP4-AS1 in HTC116 cells and animal models. Furthermore, FOXP4-AS1 served as a molecular sponge for miR-423-5p, and NACC1 is a direct target of miR-423-5p. MiR-423-5p silencing or overexpression of NACC1 increased proliferation, migration, and invasion of HCT116 cells while suppressing apoptosis. We also found that the upregulation of FOXP4-AS1 was activated by ATF3 in CRC cells. Collectively, our results demonstrated that ATF3-activated FOXP4-AS1 aggravates CRC progression by regulating miR-423-5p/NACC1 axis, indicating a new target for CRC treatment. Graphical Abstract: uf0001